Field Study on the Law of Surface Subsidence in the High-Intensity Fully Mechanized Caving Mining Working Face with Shallow Thick Bedrock and Thin Epipedon in Hilly Areas - Yi Tan; Hao Cheng; Shuang Gong; Erhu Bai; Minchao Shao; Bingyuan Hao; Xiaoshuang Li; Han Xu (Advances in Materials Science and Engineering)
Shallow and thick coal seams occur extensively in hilly areas in Shanxi Province and Shaanxi Province, China. The surface damage and landslides caused by shallow fully mechanized caving mining have a very serious impact on the environment. To provide a theoretical and reference foundation for mine environmental protection in hilly settings, a research on surface movement of the high-intensity fully mechanized caving mining working face with shallow thick bedrock and thin epipedon (HIFMCMWFSTBTE) is urgently needed. In this study, using the P2 working face of a mine as the research object, three surface subsidence observation lines were arranged in this working face to analyze the dynamic change characteristics of surface subsidence. Besides, the law of surface movement, mining sufficiency, fracture development and distribution characteristics, subsidence speed, and surface movement duration of HIFMCMWFSTBTE in hilly areas were comparatively studied. The research results reveal that the upper part of the slope slides towards the downhill direction under the action of tensile stress or push stress. As a result, the range of the horizontal movement towards the downhill direction of the slope and the range of surface movement both increase, and the movement angle and boundary angle both decrease compared with the plain. HIFMCMWFSTBTE is prone to serious sudden discontinuous damage. Fractures on the gully region surface develop along the contour, forming a crisscross fracture network, and the fractures are not easy to close after being generated. HIFMCMWFSTBTE in hilly areas can achieve full mining more easily than those of other geological conditions. According to the field measurement, critical full mining can be achieved in P2 working face when the ratio of mining width to mining depth is 1.07. The surface movement duration of HIFMCMWFSTBTE in hilly areas is relatively short. Considerable subsidence will occur in the active stage, and the surface subsidence is sudden and violent. The measured surface stabilization time of the P2 working face is only 20% of the calculated value in the Specification for Coal Pillar Reservation and Coal Mining under Buildings, Water Bodies, Railways, and Main Shafts (hereinafter referred to as the Specification), indicating that the specification's empirical formula is inapplicable to the calculation of surface stabilization time of the P2 working face.